2018
DOI: 10.1021/acs.analchem.8b03431
|View full text |Cite
|
Sign up to set email alerts
|

Toward Using Fluorescent Nanodiamonds To Study Chronological Aging in Saccharomyces cerevisiae

Abstract: One of the theories aiming to explain cellular aging is the free radical theory of aging, which describes the possible role of increased production and accumulation of free radicals. Fluorescent nanodiamonds (FNDs) are proposed to provide a tool to detect these radicals, as they function as magnetic sensors that change their optical properties depending on their magnetic surrounding. Therefore, they could enable the study of aging at a molecular level and unravel the exact role of free radicals in this process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 33 publications
(61 reference statements)
2
23
0
Order By: Relevance
“…Here we have shown that FNDs, in the longer term, do not interfere with this YAP1-mediated oxidative stress defense during chronological aging. This corresponds to the earlier reporting of no significant differences in the survival of a chronological aging cell population after treatment with CT and FNDs [13].…”
Section: Transient Fnd-induced Changes In Oxidative Stress Transcriptomesupporting
confidence: 91%
See 2 more Smart Citations
“…Here we have shown that FNDs, in the longer term, do not interfere with this YAP1-mediated oxidative stress defense during chronological aging. This corresponds to the earlier reporting of no significant differences in the survival of a chronological aging cell population after treatment with CT and FNDs [13].…”
Section: Transient Fnd-induced Changes In Oxidative Stress Transcriptomesupporting
confidence: 91%
“…In previous publications [13,16], we have shown that cells survived the presence of FND. In this paper we take biocompatibility one step further.…”
Section: Resultsmentioning
confidence: 64%
See 1 more Smart Citation
“…Thus, we surmise that for both particle types a large proportion of diamond particles is excreted from the cells. Excretion in yeast has been observed for diamond [17] as well as for other materials. The process has been described to happen when the cells are not in a balanced condition.…”
Section: Fnd Quantification After Cell Divisionmentioning
confidence: 94%
“…To achieve uptake, two protocols have been established: One option is to permeabilize the cell wall, which allows the diamond particles to enter. It has also been shown in a previous work that the cells could proliferate after being treated with FNDs [16,17]. Another option, which we used here, is to remove the cell wall entirely.…”
Section: Introductionmentioning
confidence: 97%